Comparison of two whole-body computer tomography protocols for polytrauma patients. (28th May 2021) - van Veelen, N; Studer, S; van de Wall, B; Babst, R; Link, B -C; Knobe, M; Beeres, F
Abstract: Objective: The use of whole-body computed tomography (CT) is an established standard primary diagnostic method in the work up of polytrauma patients. The protocols used for such CTs however vary between trauma centers. In our Level 1 trauma Centre the protocol was changed from a three phase to a two phase protocol with different positioning of the patient. The primary aim of this study was to compare the estimated radiation dose and scan duration of the two protocols. The secondary aim was to evaluate whether the revision of the CT protocol led to a reduction of required additional imaging of the upper extremities. Methods: For this retrospective, cross-sectional study two groups of consecutive trauma patients, which were treated in a level 1 trauma center in Switzerland and received a whole-body CT were analyzed. Group A consisted of patients, who presented between January and August 2016. These patients received a three-phased CT in which a repositioning of the arms from the side of the torso to above the head between phases two and three was needed. Group B consisted of those, who presented between January and July 2017. These patients received a CT according to a revised protocol, which was performed in two phases with the arms positioned ventral on a pillow to the torso throughout the entire CT. Scan duration, estimated radiation dose, number of upper extremity injuries, number of addition imaging (xray and CT) of the upper extremities within 24 hours of initial CT. Results: A total of 182 patients were included in group A and 218 in group B. Baseline characteristics didn't differ, except for there being more males in group B (p 0.006). The estimated radiation dose was lower (15.0 mSv vs 22.9 mSv, p < 0.001) and the scan duration shorter (4 vs 7 minutes, p < 0.001) in group B. No difference could be shown in the number of upper extremity injuries detected. Further, the number of additional images of the upper extremities needed within 24 hours of the initial CT did not differ between the groups. Conclusion: Both the estimated radiation dose and the scan duration of a whole-body CT scan in trauma patients can be reduced when a two phase protocol in which the arms are positioned on a pillow ventral to the torso is used instead of a three phase protocol with repositioning of the arms. The amount of additional imaging of the upper limb could not be reduced by having the arms visible on the scan.